Consumers’ halal products purchase: an integration of TPB - Azizan, Farah Lina; Ahmad, Zulaiha; Afendi, Noor Afzainiza (UiTM Cawangan Johor, 2022)
Halal products are becoming increasingly popular among consumers around the world, especially among Muslims. Muslim consumers are looking for a product that is fitted to their religious and society's needs. Thus, this study aims to examine the factors affecting consumers' halal products grounded by the Theory of Planned Behavior (TPB), including consumer attitudes, subjective norms, perceived behavioral control, and trust towards purchase intention. This study involved 261 Muslim consumers in the Northern region of Malaysia using a simple random sampling technique. A path model that fitted properly in the analysis was used, 12 543.14; comparative fit index (CFI) = 0.908; incremental fit index (IFI) 0.908; root mean square error approximation (RMSEA) 0.068. Path analysis of the structural model indicated a positive significant statistical relationship between consumer attitudes, subjective norm, perceived behavioral control, and trust with purchase intention.